Empowering Gen Z Economics Teachers: AI Mindset, Experiential Learning and Career Readiness for Sustainable Development - Dely Nuralizah; Eka Hendi Andriansyah; Dhiah Fitrayati; Ramlee bin Ismail (International Journal of Emerging Research and Review, 2026)
Objective: The ongoing transformation of education due to technological advances and artificial intelligence demands that prospective teachers possess change-sensitive skills and comprehensive career readiness. To support the implementation of SDGs, particularly goals 4 and 8 which include improving the quality of education as well as decent employment opportunities and economic growth. strengthening the competencies and job readiness of prospective teachers is becoming an increasingly important issue. This study seeks to examine the effect of AI mindset on the career readiness of economics education students who are preparing to become future economics teachers. Method: This study, using a PLS-SEM approach, also examines the role of experiential learning as a mediating variable in the relationship between AI mindset and career readiness. Results: This study found that an AI mindset had a positive and significant impact on career readiness, both directly and through enhanced experiential learning. These results suggest that combining an AI mindset with contextual learning experiences can strengthen students' readiness to face the demands of careers in the digital age. Novelty: Placement of experience-based learning as a mediating variable that connects AI mindset with career readiness of prospective economics teachers, especially in teacher education in Indonesia.